Cardio-cerebrovascular disease risk factors among male night-shift workers in South Korea: a comparative analysis of drivers and security guards - Jung-Min Sung; Young Joong Kang; Shinhee Ye; Eun-A Kim (International Journal of Occupational Medicine and Environmental Health, 2025)
Objectives This study investigates the prevalence of cardio-cerebrovascular disease (CCVD) risk factors among male night-shift workers in South Korea, focusing on drivers and security guards, who constitute a significant portion of the older worker population.